Reconstructing Al-Ghazali's Educational Thought: A Solution to the Spiritual Crisis in Contemporary Islamic Education - Rasmi; Marlina (IAIN KENDARI, 2025)
Modern Islamic education faces a serious challenge in the form of a spiritual crisis caused by an overemphasis on cognitive achievement and the neglect of moral and transcendental dimensions. This situation highlights the urgent need for a holistic, value-based educational model. This study aims to reconstruct the educational thought of Imam Al-Ghazali as a conceptual and practical solution to this issue. Using a descriptive qualitative approach through library research, the study analyzes Al-Ghazali’s authentic works alongside contemporary academic literature using interpretative and hermeneutic methods. The findings reveal that Al-Ghazali views education as a process of soul purification (tazkiyat an-nafs) aimed at forming complete individuals through the integration of reason (‘aql), heart (qalb), and action (‘amal). His educational framework rests on three key pillars: character formation, classification of knowledge into fardhu ‘ain (individual obligation) and fardhu kifayah (collective obligation), and a spiritually grounded teacher-student relationship. He also advocates for teaching methods based on moral exemplarity and self-reflection rather than rote memorization. Al-Ghazali’s ideas are highly relevant to contemporary Islamic education, which demands value-oriented, spiritually enriching, and contextually adaptive approaches. In conclusion, Al-Ghazali’s educational philosophy offers a solid foundation for designing an integrative Islamic education system capable of addressing modern spiritual challenges.